OPTIMIZATION OF ACUTE MYOCARDITIS TREATMENT - Svetlana A. Chepurnenko; Galina V. Shavkuta; Alina D. Nasytko (Кубанский научный медицинский вестник, 2019)
Aim. This paper is aimed at investigating the possibility of preventing an adverse outcome of acute viral myocarditis by means of optimal pharmacotherapy without the use of surgical treatment methods.Results. We describe a clinical case of acute viral myocarditis in a 60-year old female patient. According to the conducted echocardioscopy, the dilatation of the heart cavities and the complete insufficiency of the mitral and tricuspid valves were identified. A cumulative effect of the chosen optimal pharmacotherapy, which included an angiotensin converting enzyme inhibitor, a beta-blocker, a mineralocorticoid receptor antagonist and a loopback diuretic with neurohumoral properties taken in optimal doses, allowed congestion signs to be rapidly eliminated, a reverse remodeling of the heart to be achieved and the heart size to be returned normal values. The double blockade of aldosterone receptors using eplerenone and torasemide prevented both the development of fibrosis in the myocardium and the formation of irreversible dilated cardiomyopathy.Conclusion. The application of antiviral and immunomodulatory therapy, along with the maximum possible doses of drugs used to treat chronic heart failure, allowed the patient’s cardiohemodynamic parameters to be returned to normal values. A timely combination therapy should be used to avoid the formation of dilated cardiomyopathy, thus improving the prognosis of the disease.